RIFA'IYAH ISLAMIC COMMUNITY’S ACCOMMODATIVE POLITICS IN KUDUS - Rosyid, Moh (Jurnal Politik Profetik, 2022)
The Rifa'iyah Islamic Community was established by Kiai Ahmad Rifa'i since the Dutch colonial era. This community used the Javanese Book of Tarjumah Pegon as a means of confrontation against colonialism. This article elaborates Rifa’iyah’s political strategy and how this community keeps existing in the present era. The research has an objective to discuss this community’s political strategy, its existence and the dynamic as an Islamic community in Kudus. The paper uses interview as the main method, as well as observation and documentation using history analysis and accommodation theory. The findings of this research that at the starting point of Rifa'iyah community, it was rejected by residents because of differences in worship based on the teachings of the Book of Tarjumah, for example, praying only with fellow Rifa'iyah members, practicing wedding ceremony based on Rifa'iyah guidance, and only studying the book by Kiai Rifa'i. However, its existence is now accepted due to the accommodating strategy of Rifa'iyah pilgrims. Adaptive political efforts are carried out by the Rifa'iyah community in Kudus to exist and be accepted, for example, by doing proactive steps in the fields of government, social, and culture.